KWL (Know, Want to Know, Learned) Strategy for Teaching English Reading Comprehension In Efl Classroom - Nurfadilah, Nufadilah (Al-Iftah: Journal of Islamic studies and society, 2021)
KWL is a teaching strategy. The approximate acronym stands for what I know, what I want to know, and learned. The teachers used KWL strategy as a reading comprehension aid. This study aimed to find out the teachers’ creativity toward KWL strategy in EFL classroom. Next, to know the teachers’ perception toward KWL strategy in teaching reading comprehension in EFL classroom. This research used qualitative data. It is obtained from the result of interview and observation. The techniques of analyzing data were reduction the data, data analysis, presenting the data, and drawing conclusion. The respondent of this study was five English teachers at MTs in Sidrap Regency. The researcher used interview and observation in collecting the data. The interview is used to know the teachers’ perspective for teaching students through KWL strategy, and the observation is used to know the teachers’ creativity for teaching reading comprehension in EFL classroom. The result of this study show that teachers’ creativity is categorized into three, they are: progress creativity, decline creativity and unchanged creativity. Meanwhile, teachers’ perception toward KWL strategy is related to: teachers’ perception about implementation KWL strategy, and teachers’ perception toward advantages in implementing KWL strategy. It is proved by the interviewed that has given to the teachers and observation that the researcher found in the field.